STUDI LITERATURE: TANAMAN OBAT HERBAL UNTUK PENYEMBUHAN BATUK DAN FLU - Oashttamadea, Ressa; Maiyonti, Puja (AKADEMI PEREKAM DAN INFORMASI KESEHATAN (APIKES) IRIS PADANG, 2024)
Coughing is a reflex that is stimulated by irritation of the lungs or respiratory tract. The aim of this research is to determine the benefits of herbal medicinal plants for curing coughs and flu and aims to reveal and convey the types/species of plants used in treating coughs and flu. The method used for literature studies is an article review by searching several national published journals via the database: Google Scholar. The keywords used are